Análise do consumo de linha de costura para os tipos de pontos 512 e 602 - Vendrame, Gabriela Viana (2021)
The sewing thread is one of the most used raw materials in a clothing industry. It has a direct influence on the sewing quality of a textile article, thus, industries must plan the amount of sewing thread to acquire, to avoid material and stock losses. To perform the calculations for determining thread consumption, impractical methods are applied or tables are used with predetermined consumption values for generic clothing items, where they do not clearly state the possible seam variations present as yarn titration, thread type, fabrics, number of layers applied and stitch density per centimeter, resulting in uncertain values. This work aimed at the development of a practical and dynamic calculation method to determine the consumption of sewing thread through the collection of linear mass for textile yarns for points 512 and 602. The results obtained showed that the consumption of thread for of the sewing of the types of stitches analyzed was influenced by different types of fabrics with different weights, layers and stitch density.